2016
DOI: 10.1111/cen.13089
|View full text |Cite
|
Sign up to set email alerts
|

Neutral associations of testosterone, dihydrotestosterone and estradiol with fatal and non‐fatal cardiovascular events, and mortality in men aged 17–97 years

Abstract: In predominantly middle-aged men, T, DHT and E2 do not influence mortality or CVD outcomes. This neutral association of hormones with CVD contrasts with prior studies of older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…Previous epidemiological studies have assessed associations of either PA or hormone levels with outcomes related to cardiometabolic health, but not analysed for interactions between the two. Some studies have adjusted for PA when examining hormones vs cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies have assessed associations of either PA or hormone levels with outcomes related to cardiometabolic health, but not analysed for interactions between the two. Some studies have adjusted for PA when examining hormones vs cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that either low oestradiol levels, or high oestradiol levels were associated with increased mortality. There are also studies showing no association between endogenous oestradiol and all‐cause mortality . Possible explanations for these inconsistencies might be differences in subjects’ characteristics, numbers of events and adjustment for different covariates.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies showing no association between endogenous oestradiol and all-cause mortality. [11][12][13][14] Possible explanations for these inconsistencies might be differences in subjects' characteristics, numbers of events and adjustment for different covariates. Negative results tended to be more frequently observed in studies based on middle-aged men 11,12,14 ; biological effects of oestradiol might be more prominent in older men, or low mortality rates in middle-aged men may have led to insufficient statistical power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high levels of luteinizing hormone were positively associated with AAA outcomes [62]. Interestingly, lower testosterone levels have been linked to coronary artery disease and peripheral arterial disease in older men, but show litle association when grouped with younger men [63][64][65].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 99%